Learning by Teaching, Why Not? - Sri Damayanti; Sri Hastuty; Juwita Crestiani; Alim Surya Saruman; Irwan Irwan (Jurnal Studi Guru dan Pembelajaran, 2018)
Lesson Study for Learning Community was held by applying Magang Based Lesson Study at Universitas Cokroaminoto Palopo. There were ten Students collaborated with 4 lecturers and 4 teachers. Those teachers are the teachers at SMP Negeri 1 Palopo, SMP Negeri 2 Palopo, SMP Cokroaminoto Palopo, and a teacher at SMA Negeri 6 Palopo. This paper aimed is describing the students’ activities in learning by teaching and how they prepare their class. The research question of this paper is what are the students’ activities in preparing their class? How do the students’ prepare their class? What Lesson learned found in Magang Based Lesson Study? In answering the research question, the researcher conducted a research in a year by participating in learning community. Although this research has not finished yet, she describes that the students who conducted Magang prepared their class by learning how do their students learn. After that, they discussed it by collaborating with lecturers at Universitas Cokroaminoto Palopo. In doing teaching in classroom, the rest of the students observed the students’ way in learning. It is about when do the students start to focus on studying, how did they learn collaboratively with their groups.